2010
DOI: 10.1089/ten.tec.2009.0053
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Generation of Thick, Vascularized Hepatic Tissue from Collagen Hydrogel-Based Hepatic Units

Abstract: In vivo engineering of hepatic tissue based on primary hepatocytes offers new perspectives for the treatment of liver diseases. However, generation of thick, three-dimensional liver tissue has been limited by the lack of vasculature in the tissue-engineered constructs. Here, we used collagen hydrogel as a matrix to generate engineered hepatic units to reconstitute three-dimensional, vascularized hepatic tissue in vivo. Hepatocytes harvested from Sprague-Dawley rats were mixed with liquid type I collagen, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…This task becomes more complicated when the target tissue is vascularized and composed of a hierarchical organization of heterogeneous tissues. Successful proof of the IVB principle has been shown for complex tissues such as the trachea (Tsao et al, 2014), full-thickness skin (Eriksson and Vranckx, 2004), bladder (Baumert et al, 2007b), esophagus (Badylak et al, 2011), and skeletal muscle (Bitto et al, 2013); and for organs such as the liver (Zhao et al, 2010), heart (Ott et al, 2008), and lung (Wu et al, 2013). However, the unmet clinical demands in these areas and the barriers to clinical translation in existing demonstrations are well known.…”
Section: Discussion: Future Trends and Challengesmentioning
confidence: 99%
“…This task becomes more complicated when the target tissue is vascularized and composed of a hierarchical organization of heterogeneous tissues. Successful proof of the IVB principle has been shown for complex tissues such as the trachea (Tsao et al, 2014), full-thickness skin (Eriksson and Vranckx, 2004), bladder (Baumert et al, 2007b), esophagus (Badylak et al, 2011), and skeletal muscle (Bitto et al, 2013); and for organs such as the liver (Zhao et al, 2010), heart (Ott et al, 2008), and lung (Wu et al, 2013). However, the unmet clinical demands in these areas and the barriers to clinical translation in existing demonstrations are well known.…”
Section: Discussion: Future Trends and Challengesmentioning
confidence: 99%
“…Although collagen has arginine-glycine-aspartic acid (RGD) sequence as the recognition site instead of galactose, collagen gels were used in hepatocyte culture for the application of bioartificial liver (Zhao et al 2010b). The results indicated that the collagen gels reconstituted a 3D vascularized hepatic tissue in vivo although they have weak mechanical property.…”
Section: Liver In Vitro Models In Pharmacology Toxicology and Basic mentioning
confidence: 99%
“…The first is to use a scaffold that mimics the extracellular matrix (ECM) to immobilize cells and to construct the 3-D cell stacks. 12 Many porous scaffolds have been developed for this purpose such as those made of poly(d,l-lactide-co-glycolide) (PLGA), 13 hyaluronic acid, 14 collagen, 15,16 polyacrylic acid (PAA), 17 poly(ethylene glycol), 10 chitosan, 18 alginate, 19,20 and others. [21][22][23] These scaffolds can immobilize cells and support cell growth.…”
Section: Introductionmentioning
confidence: 99%